Pengaruh Lokasi, Harga, Dan Estetika Produk Terhadap Keputusan Pembelian Di Toko Plastik Sumber Rejo Malang. - Khafili, Moch Farid Khafizd; Wahono, Budi; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to determine how much influence price, location, and aesthetics have on purchasing decisions at Sumber Rejo plastic shop. The sampling technique uses Simple Random Sampling technique and the results obtained are 95 respondents. Data obtained by distributing questionnaires to customers of Sumber Rejo Plastic Shop, Data analysis in this study used SPSS. The data testing techniques used in this study include validity test, reliability test, normality test, classical assumption test, multiple linear regression analysis test, f test, t test and multiple determination coefficient test (R2). The results of this study indicate that location and aesthetics have a significant positive effect on purchasing decisions. Meanwhile, price has a significant negative effect on purchasing decisions.. Keywords: Effect of Location, Price, and Aesthetics on Purchasing Decisions